Peran Pajak sebagai Instrumen Kebijakan Fiskal untuk Meningkatkan Pendapatan Daerah di Polewali Mandar - Juhura (Al Rikaz: Jurnal Ekonomi Syariah, 2025)
Tax is one of the main instruments in fiscal policy that has a strategic role in increasing regional income. This study aims to analyze the role of tax as a fiscal policy instrument in increasing regional income in Polewali Mandar. The research method used is a qualitative approach with data collection through interviews, documentation studies, and direct observation. The results of the study indicate that the optimization of tax revenue in Polewali Mandar is influenced by the effectiveness of tax administration, public awareness of tax obligations, and information technology support. The discussion shows that there is great potential for increasing regional income through tax reform, increasing the capacity of tax officials, and increasing community participation. The conclusion of this study is that tax has a significant role as a fiscal policy instrument in increasing regional income in Polewali Mandar, but synergistic efforts are needed between the local government, tax officials, and the community to achieve optimal results.